2015
DOI: 10.1007/s11427-014-4788-x
|View full text |Cite
|
Sign up to set email alerts
|

RGK regulation of voltage-gated calcium channels

Abstract: Voltage-gated calcium channels (VGCCs) play critical roles in cardiac and skeletal muscle contractions, hormone and neurotransmitter release, as well as slower processes such as cell proliferation, differentiation, migration and death. Mutations in VGCCs lead to numerous cardiac, muscle and neurological disease, and their physiological function is tightly regulated by kinases, phosphatases, G-proteins, calmodulin and many other proteins. Fifteen years ago, RGK proteins were discovered as the most potent endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In excitable cells, plasma membrane depolarization activates voltage-gated Ca 2+ channels to initiate cytosolic Ca 2+ concentration elevation, which in turn regulates many physiology processes, including muscle contraction, gene transcription, synaptic transmission and so on (Catterall, 2011, Buraei et al, 2015). A recent study, however, unexpectedly found the presence of the pore-forming α1A subunits of voltage-gated Ca 2+ channels in lysosomes of both fruit flies and mice (Tian et al, 2015).…”
Section: Ion Homeostasis and Ion Channels In The Lysosomesmentioning
confidence: 99%
“…In excitable cells, plasma membrane depolarization activates voltage-gated Ca 2+ channels to initiate cytosolic Ca 2+ concentration elevation, which in turn regulates many physiology processes, including muscle contraction, gene transcription, synaptic transmission and so on (Catterall, 2011, Buraei et al, 2015). A recent study, however, unexpectedly found the presence of the pore-forming α1A subunits of voltage-gated Ca 2+ channels in lysosomes of both fruit flies and mice (Tian et al, 2015).…”
Section: Ion Homeostasis and Ion Channels In The Lysosomesmentioning
confidence: 99%
“…Thus, we cannot exclude that beneath singlechannel activity, VGCC expression might be affected by the examined Ca V β variant. RGK-proteins in general are known VGCC inhibitors by directly inhibiting the activity of VGCCs or altering number of channels at the membrane (Buraei et al 2015). While some of the RKG-proteins can regulate VGCC activity by directly interacting with the pore-forming subunit of VGCC complexes, Gem utilizes a solely Ca V β-dependent mode of action (Puckerin et al 2016(Puckerin et al , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway controlled by rapid electrical signaling (action potential) is mainly mediated by the voltage-gated Ca 2+ (Ca v ) channels. There are a number of Ca v channels that vary in tissue and cell distribution, conductivity, and voltage sensitivity [6]. Auxiliary Ca v β subunits are known to associate with the pore-forming Ca v α subunits to modify the flavor of channel properties.…”
Section: Ca 2+ Homeostasis (Figure 2)mentioning
confidence: 99%
“…Further, a family of GTPase molecules called RGKs bind to Ca v channels and regulate their expression and biophysical properties. This is reviewed by Yang Jian and colleagues [6].…”
Section: Ca 2+ Homeostasis (Figure 2)mentioning
confidence: 99%